Low-overhead distribution strategy for simulation and optimization of large-area metasurfaces - Ahmad-Stein, D. (Nature Research, 2022)
Fast and accurate electromagnetic simulation of large-area metasurfaces remains a major obstacle in automating their design. In this paper, we propose a metasurface simulation distribution strategy which achieves a linear reduction in the simulation time with the number of compute nodes. Combining this distribution strategy with a GPU-based implementation of the Transition-matrix method, we perform accurate simulations and adjoint sensitivity analysis of large-area metasurfaces. We demonstrate ability to perform a distributed simulation of large-area metasurfaces (over 600λ × 600λ), while accurately accounting for scatterer-scatterer interactions significantly beyond the locally periodic approximation. © 2022, The Author(s).